Three-dimensional imaging of the P- and S-wave velocity structure and earthquake locations beneath Southwest Iceland - Tryggvason, Ari; Rögnvaldsson, Sigurður Th.; Flóvenz, Ólavur G. (Geophysical Journal International, 2002)
Using local earthquakes and explosions recorded on the 3-D seismic network operating in Southwest Iceland, the 3-D velocity structure has been modelled to depths of 10–15 km. The tomography algorithm simultaneously inverts for both P - and S -wave velocities and hypocentral locations. Major tectonic features within the 224 × 112 km2 rectangular study region include the South Iceland Seismic Zone, the Hengill volcanic system and the Reykjanes Volcanic Zone. Reduced velocities from the surface to as deep as we can resolve, or about 9 km, are associated with the Hengill central volcano. As low Vp/Vs ratios prevail in the entire anomalous region, we suggest supercritical fluids within the volcanic fissure system cause the reduced velocities, rather than any large regions of partial melt. Along the Reykjanes Volcanic Zone, relatively low velocities down to depths of 6–8 km are observed in the centre of the zone. Normal velocities are observed in the South Iceland Seismic Zone with a slight reduction in Vp/Vs ratio. The thickness of the brittle crust, defined as the depth above which 90 per cent of the earthquakes occur, increases from about 5 km in the relatively young crust of the Reykjanes Volcanic Zone to about 12 km in the eastern end of the South Iceland Seismic Zone. These depths correspond to temperatures in the range of 580–750°C, estimated from borehole heat flow measurements.